2016
DOI: 10.1002/jmri.25194
|View full text |Cite
|
Sign up to set email alerts
|

Intravoxel incoherent motion diffusion‐weighted imaging of hepatocellular carcinoma: Is there a correlation with flow and perfusion metrics obtained with dynamic contrast‐enhanced MRI?

Abstract: Purpose To assess the correlation between intravoxel incoherent motion diffusion-weighted imaging (IVIM-DWI) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) metrics in hepatocellular carcinoma (HCC) and liver parenchyma. Materials and Methods Twenty-five patients with HCC (M/F 23/2, mean age 58 years) underwent abdominal MRI at 1.5 or 3.0T, including IVIM-DWI (with 16 b-values) and DCE-MRI (3D FLASH sequence, mean temporal resolution of 2.3 sec). IVIM-DWI parameters (pseudodiffusion coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 41 publications
4
49
2
Order By: Relevance
“…However, they reflect different aspects of perfusion: D* is related to the length and velocity of the capillary network, whereas f reflects the fraction of the microcirculation that accounts for all diffusion in voxels. Unsurprisingly, several studies have observed similar mismatches for D* and f (29,(31)(32)(33), even in dynamic contrast enhancement research (34), which is another type of perfusion-related hemodynamic model. One convincing explanation for this contradiction is that f is dependent on echo time (TE): the longer the TE, the larger the f value.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, they reflect different aspects of perfusion: D* is related to the length and velocity of the capillary network, whereas f reflects the fraction of the microcirculation that accounts for all diffusion in voxels. Unsurprisingly, several studies have observed similar mismatches for D* and f (29,(31)(32)(33), even in dynamic contrast enhancement research (34), which is another type of perfusion-related hemodynamic model. One convincing explanation for this contradiction is that f is dependent on echo time (TE): the longer the TE, the larger the f value.…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, it should be noted that it is imprecise to fit the bi-exponential model for too few b values, although one report confirmed that only four b values were sufficient to estimate IVIM parameters (41). The SD or CV of D* is frequently large and is well known for its worse reproducibility and repeatability compared with the other three parameters (21,34,42,43). In spite of significant differences in the D* values between HCC and FNH, its efficacy was inferior to ADC total and D, as is generally accepted.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of rejecting data points, perform motion correction is Other post-processing technique such as image denoising and registration may also be helpful for IVIM quantification. These processing could potentially be more effective if it is applied on the images of the individual directions before averaging or directly on the raw data, which has not been attempted with IVIM study (35). However, it should be noted that the noise characteristics on MR magnitude images are much dependent on many factors of hardware, acquisition and reconstruction.…”
Section: Image Post-processing Methods For Ivim Parametersmentioning
confidence: 99%
“…These shifts of phase in turn depend not only on the magnetic field but also on, among others, the K-space acquisition ordering mode, image resolution, acquisition segmentation, and receiver bandwidth. (35) reported that there was no information overlap (or can be interpreted as poor correlation) between IVIM parameters and dynamic contrast enhanced (DCE) MRI metrics.…”
Section: Ivim Parameters Of Healthy Liver In Published Literaturesmentioning
confidence: 99%
“…However, one of the issues highlighted to date is the poor test–retest variability of f and D*, on the order of >100% in some cancers, eg, rectal . There also appears some contention as to technical/biological correlates: while some studies have shown a relationship between IVIM and DCE‐MRI parameters, others have not in some cancers, eg, hepatocellular carcinoma . One also has to be aware that flow from glandular secretions, eg, pancreas, may be difficult to separate from micro‐capillary perfusion.…”
Section: Emerging Mri Biomarkersmentioning
confidence: 99%